Prognostic Significance of Serum Free Amino Acids in Head and Neck Cancers - Vsiansky, Vit; Svobodova, Marketa; Gumulec, Jaromir; Cernei, Natalia; Sterbova, Dagmar; Zitka, Ondrej; Kostrica, Rom; Smilek, Pavel; Plzak, Jan; Betka, Jan; Kalfert, David; Masarik, Michal; et al. (Cells, 2019)
Despite distinctive advances in the field of head and neck squamous cell cancer (HNSCC) biomarker discovery, the spectrum of clinically useful prognostic serum biomarkers is limited. As metabolic activities in highly proliferative transformed cells are fundamentally different from those in non-transformed cells, specific shifts in concentration of different metabolites may serve as diagnostic or prognostic markers. Blood amino acids have been identified as promising biomarkers in different cancers before, but little is known about this field in HNSCC. Blood amino acid profiles of 140 HNSCC patients were examined using high-performance liquid chromatography. Cox proportional hazards regression model was used to assess the prognostic value of amino acid concentrations in serum. Colony forming assay was used to identify the effect of amino acids that were significant in Cox proportional hazards regression models on colony forming ability of FaDu and Detroit 562 cell lines. In the multivariable Cox regression model for overall survival (OS), palliative treatment was associated with an unfavourable prognosis while high serum levels of methionine have had a positive prognostic impact. In the relapse-free survival (RFS) multivariable model, methionine was similarly identified as a positive prognostic factor, along with tumor localization in the oropharynx. Oral cavity localization and primary radio(chemo)therapy treatment strategy have been linked to poorer RFS. 1mM serine was shown to support the forming of colonies in both tested HNSCC cell lines. Effect of methionine was exactly the opposite.
Keywords: Kaplan-Meier Estimate; Tumor Stem Cell Assay; Female; multivariační analýza; amino acids; ženské pohlaví; Kaplanův-Meierův odhad; Multivariate Analysis; colony forming assay; testy nádorových kmenových buněk; nádory hlavy a krku; lidé; Aged, 80 and over; prognóza; head and neck cancer; blood biomarkers; Head and Neck Neoplasms; Male; Aged; Prognosis; lidé středního věku; senioři nad 80 let; Amino Acids; senioři; mužské pohlaví; aminokyseliny; Middle Aged; prognosis; metabolism; Humans